Lymphoma in patients treated with anti-TNF: results of the 3-year prospective French RATIO registry. Issue 2 (14th October 2009) - Mariette, X; Tubach, F; Bagheri, H; Bardet, M; Berthelot, J M; Gaudin, P; Heresbach, D; Martin, A; Schaeverbeke, T; Salmon, D; Lemann, M; Hermine, O; et al.
Abstract : Objective: To describe cases of lymphoma associated with anti-TNF therapy, identify risk factors, estimate the incidence and compare the risks for different anti-TNF agents. Methods: A national prospective registry was designed (Research Axed on Tolerance of bIOtherapies; RATIO) to collect all cases of lymphoma in French patients receiving anti-TNF therapy from 2004 to 2006, whatever the indication. A case–control analysis was conducted including two controls treated with anti-TNF per case and an incidence study of lymphoma with the French population was used as the reference. Results: 38 cases of lymphoma, 31 non-Hodgkin's lymphoma (NHL) (26 B cell and five T cell), five Hodgkin's lymphoma (HL) and two Hodgkin's-like lymphoma were collected. Epstein–Barr virus was detected in both of two Hodgkin's-like lymphoma, three of five HL and one NHL. Patients receiving adalimumab or infliximab had a higher risk than those treated with etanercept: standardised incidence ratio (SIR) 4.1 (2.3–7.1) and 3.6 (2.3–5.6) versus 0.9 (0.4–1.8). The exposure to adalimumab or infliximab versus etanercept was an independent risk factor for lymphoma in the case–control study: odds ratio 4.7 (1.3–17.7) and 4.1 (1.4–12.5), respectively. The sex and age-adjusted incidence rate of lymphoma was 42.1 per 100 000 patient-years. The SIR was 2.4 (95% CI 1.7 to 3.2). Conclusion: The two to threefold increased risk of lymphoma in patients receiving anti-TNF therapy is similar to that expected for such patients with severe inflammatory diseases. Some lymphomas associated with immunosuppression may occur, and the risk of lymphoma is higher with monoclonal-antibody therapy than with soluble-receptor therapy.